Evaluation of knowledge, attitude and practices of postgraduate medical students towards clinical research in a tertiary care teaching hospital - Johar, Sukhmeen Kaur; Jaybhaye, Deepali L.; Chandra, Shruti; Mishra, Prashant S. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Clinical research is a component of medical and health research that facilitates valuable knowledge regarding diagnosis, prevention as well as treatment of a disease. Nowadays, the practise of medicine is evidence-based and combining medical education with clinical research provides a channel for translating scientifically advanced knowledge into better public health. The aim of the study was to assess knowledge (K), attitude (A), and practices (P) about clinical research among post graduate medical students. Methods: After obtaining institutional ethics committee approval, a cross-sectional and questionnaire-based study was conducted. A pre-structured and validated KAP questionnaire comprising of 25 questions (knowledge-15, attitude-5 and practices-5) was shared online through google forms with post graduate students. The responses to the questions were later marked correct or incorrect. The data was collected and compiled using Microsoft excel and expressed in percentage (%). Data analysis was performed using SPSS version 25.0. Results: 102 students responded to the questionnaire completely. Out of which males (55.9%) pre-dominated and majority of the PG students belonged to I year accounting for 40.2%. About 61.76% PG students were aware about a clinical research unit in the college. Majority of the students acknowledged the necessity of conducting clinical research and exhibited good knowledge about key concepts of clinical trials. Even responses to questions pertaining to attitude towards clinical research were also majorly positive. On the contrary, more than 90% students had neither attended any workshop on ICH-GCP guidelines nor registered their academic study under clinical trial registry of India. However, 73.5% of them expressed their willingness to participate in a clinical trial in future. Conclusions: Although, assessment of knowledge and attitudes about clinical research among post graduate students showed positive results but discrepancies were observed in its practise. As such, this necessitates incorporation of clinical research activities into existing medical education system.